A concise manual of pathogenic microbiology - Mishra, Saroj (Saroj K.) (Wiley-Blackwell, 2013)
"A Concise Manual of Pathogenic Microbiology is a quick and concise source of information on the causal agents of common infectious diseases. Divided into chapters based on broad taxonomic groupings or similarities between the causal agents, A Concise Manual of Pathogenic Microbiology lists important pathogenic taxa in each group, their natural habitats, the diseases they cause, microbiological highlights, laboratory diagnosis, and measures of prevention and control, including availability of vaccines and effective therapeutic agents"--